Global research trends and focus on the link between neutrophil extracellular traps and tumor: a bibliometric and visualization analysis from 2006 to 2024 - Xiao, Chaoyue; Feng, Xiang; Zhao, Zengyi; Ding, Gouping; Gao, Yawen (Frontiers in Immunology, 2024)
Background: Neutrophil extracellular traps (NETs) have long been consistently adjudged as an innate immunity defending against foreign pathogens, but this oversimplified view has decelerated the progression of perceiving NET biology in chronic diseases. It is now increasingly accepted that NETs are not exclusive to anti-infection response but are also central players with a double-edged sword role in cancer progression. Gradually, NETs have emerged as a tumor diagnostic, predictive, and prognostic biomarker, and even strenuous endeavors have been devoted to tapping their potential as new therapeutic targets. Correspondingly, the boom of studies on NETs and tumor in recent years has achieved a series of scientific outputs, which opens up a new perspective for perceiving the sophisticated landscapes of tumor immune microenvironment. Yet it remains much left to translate NET-targeted immunotherapies into clinical practice. Therefore, it is greatly necessary to explore the knowledge structure and latent hotspots of link between NETs and tumor by bibliometric analysis. Methods: Publications about NETs and tumor from 2006 to 2024 were extracted from the Web of Science Core Collection. Bibliometric analysis and visualization were conducted by tools encompassing Microsoft Excel, VOSviewer, CiteSpace, and R-bibliometrix. Results: The analysis includes 1339 publications authored by 7747 scholars affiliated with 1926 institutions across 70 countries/regions, with relevant articles published in 538 journals. Despite China’s maximum quantity of publications, the United States has continued to dominate the field as a global cooperation center with overwhelming citation counts. FRONTIERS IN IMMUNOLOGY published the most publications, whereas BLOOD is the highest co-cited journal. Wagner, Denisa D. and Kaplan, Mariana J. are concurrently in both the top 10 most prolific authors and cited authors lists. Tumor microenvironment and immunotherapy will likely be the focus of future research. Conclusions: A comprehensive bibliometric analysis is first conducted to map the current landscape and knowledge structure of link between NETs and tumor in the hope of proffering guidance and fresh perspectives for further research in this field. NETs are promising anti-tumor targets, and perhaps the eventual destination in the realm is to translate NET-targeted immunotherapies into clinical practice.